2014
DOI: 10.1103/physreva.89.053838
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optomechanics in the stationary regime

Abstract: We have observed nonlinear transduction of the thermomechanical motion of a nanomechanical resonator when detected as laser transmission through a sideband unresolved optomechanical cavity. Nonlinear detection mechanisms are of considerable interest as special cases allow for quantum nondemolition measurements of the mechanical resonator's energy. We investigate the origin of the nonlinearity in the optomechanical detection apparatus and derive a theoretical framework for the nonlinear signal transduction, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 59 publications
1
86
0
Order By: Relevance
“…where the thermo-optical effects have been written into a nonlinear detuning parameter ∆ nl [31,32]. This parameter can be thought of as the shift in the optical resonance frequency per intracavity photon, and is related to the parameters in Equation (4) by ∆ nl n cav = b(T )∆T , under the assumption that the temperature gradient ∆T is proportional to the number of intracavity photons.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…where the thermo-optical effects have been written into a nonlinear detuning parameter ∆ nl [31,32]. This parameter can be thought of as the shift in the optical resonance frequency per intracavity photon, and is related to the parameters in Equation (4) by ∆ nl n cav = b(T )∆T , under the assumption that the temperature gradient ∆T is proportional to the number of intracavity photons.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Nonlinearities can also arise from spatial, mechanical effects, by engineering, for example, a light-matter interaction of the form (â+â † )(G 1x +G 2x 2 ). Previous studies investigated the static shift in the cavity resonant frequency [9,14,15] or the quadratic optical spring effect [15] arising from a nonlinear coupling. However, these studies identified the problem of a residual linear G 1 contribution to the coupling.…”
mentioning
confidence: 99%
“…This is what we expect for the PSD of the squared displacement [5,9], the physical meaning of which will become more apparent when we look at the quantum case in Section VI B.…”
Section: A Classicalmentioning
confidence: 88%
“…For moderate coupling, a simple linear model suffices, such that monitoring the * Electronic address: bhauer@ualberta.ca † Electronic address: jdavis@ualberta.ca electromagnetic field provides a readout of the linear motion of the oscillating mechanical device. However, as the interaction strength between the two systems increases, nonlinear coupling begins to occur, requiring that higherorder terms be added to the Hamiltonian [3][4][5][6][7][8][9]. This provides a method by which one can obtain direct access to higher-order powers of the mechanical resonator's motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation